A pulmonary embolism case presenting with upper abdominal and flank pain - DENİZBAŞI ALTINOK, ARZU (LIPPINCOTT WILLIAMS & WILKINS, 2003)
Background The clinical manifestations of pulmonary thromboembolism are non-specific, which makes this condition difficult to diagnose. A case of helical computerized tomography angiographically documented pulmonary thromboembolism, which initially presented as upper abdominal and flank pain, is described. Case report A 46-year-old woman was referred to the emergency department for left flank and upper abdominal pain with diaphoresis and nausea. Her history included rheumatoid arthritis 3 years previously. During her examination the only abnormal finding was abdominal tenderness at the right upper quadrant and a positive Murphy sign without other systemic signs. A chest radiograph demonstrated an atelectatic line at the left lung base. The alveolar-arterial gradient was increased, and a ventilation-perfusion scan revealed a mismatch at the left upper and lower lobes, indicative of pulmonary thromboembolism. Helical computerized tomography angiography revealed filling defects on that side. The patient received anticoagulant therapy and gradually improved. Conclusion The pathogenesis of the pain in the flank and upper abdomen is not known in this case. Unexplained upper abdomen and flank pain in a patient with risk factors for pulmonary thromboembolism, such as rheumatoid arthritis, should be investigated to rule out this treatable but potentially fatal condition. (C) 2003 Lippincott Williams & Wilkins.
Keywords: Abdominal pain; computerized tomography angiography; pulmonary thromboembolism